THE INFLUENCE OF QUIZIZZ-BASED PROJECT LEARNING MEDIA ON THE LEARNING MOTIVATION OF VOCATIONAL BASICS FOR 11TH GRADE STUDENTS INTHE ONLINE BUSINESS AND MARKETING DEPARTMENT AT STATE VOCATIONAL HIGH SCHOOL 13 MEDAN - Pinta Ayu Sagala; Lenti Susanna Saragih (International Journal of Teaching and Learning, 2024)
This research aims to determine whether the use of Quizizz-Based Project Learning Media has an effect on the Learning Motivation of Vocational Basics for 11th Grade Students in the Online Business and Marketing Department at State Vocational High School 13 Medan. The results of the research have been tested for classical assumptions such as normality assumption and paired sample t-test. The research findings indicate that the proposed hypothesis is accepted as it shows positive and significant results in the hypothesis testing. It can be concluded that Quizizz-based project learning media significantly influences the learning motivation of vocational basics for 11th-grade students in the online business and marketing department at State Vocational High School 13 Medan.